SATYAM SIVAM SUNDARAM: ESENSI KEBENARAN, KEBAJIKAN, DAN KEINDAHAN DALAM SIMBOL TARIAN SIVA NATARAJA SEBAGAI HUKUM SEMESTA - I Ketut Donder; Prasanthy Devi Maheswari; Jyothi Devi Krishnanandayani (Sanjiwani: Jurnal Filsafat, 2025)
Humans are the most perfect of all creatures, because only humans possess the ability to distinguish between the eternal and the transient. Furthermore, humans possess the awareness that they are not a material body, but the Atman, which is identical with Brahman. Advaita Vedanta theology and philosophy teach that Brahman pervades the universe. Therefore, Brahman and the Universe and all its contents are one. The Universe and all its contents are the material body of Brahman. Therefore, a practical understanding of Brahman can be observed through the Rtams, or Laws of Nature.Awareness of the Atman in humans is paramount in human life. Through awareness of the Atman, humans understand the existence of God behind all things. Awareness of the Atman makes humans wise, able to perceive God's presence in all things, as the Chandogya Upanisad states, "sarva khalv idam brahman," meaning "everything is God." Thus, Advaita Vedanta teaches that God, as the Subtle Substance, permeates all atomic particles of the Universe. Thus, all natural phenomena are a Cosmic Dance known as the Sivanataraja Dance or the Tandava Dance. Therefore, Rtam, or the Laws of Nature, can be used as a medium of contemplation to discover the traces of the Creator behind all natural phenomena.This research is qualitative, with data in the form of a summary of words obtained through literatures. Using Symbol Theory and Qualitative Interpretive Analysis, the authors conclude that the Laws of Nature are a manifestation of the dance of universal Truth (Satyam), which possesses the values of universal Virtue (Sivam) and universal Beauty (Sundaram). Humans who possess a perspective in accordance with the teachings of Advaita Vedanta will be able to see and experience the world and all its natural phenomena as an expression of Satyam, Sivam Sundaram, or a blissful Heaven.